2015
DOI: 10.1007/s13224-015-0768-8
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Outcome During an Era of Active Management for Obstetrics Cholestasis

Abstract: Objective To study the incidence, maternal, and perinatal outcomes in intrahepatic cholestasis of pregnancy with active management. Materials and Methods This observational study included 48 cases diagnosed as intrahepatic cholestasis of pregnancy. Medical treatment and active management (fetal surveillance and termination of pregnancy at 37-38 weeks) were offered to all. Maternal and perinatal outcomes are studied. Results Incidence of ICP was 2.4 %. More than 86 % of patients presented with generalized pruri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 11 publications
(19 reference statements)
5
8
0
1
Order By: Relevance
“…The result of our study are comparable to the study done by Sharma N et al, although some studies reported relatively higher mean age. 10,11 Most of the women presented after 30 weeks of gestation which is similar to other study findings. 12 Generalised pruritus was the most common symptom with biochemical alterations of elevated serum bile acid and transaminase.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The result of our study are comparable to the study done by Sharma N et al, although some studies reported relatively higher mean age. 10,11 Most of the women presented after 30 weeks of gestation which is similar to other study findings. 12 Generalised pruritus was the most common symptom with biochemical alterations of elevated serum bile acid and transaminase.…”
Section: Discussionsupporting
confidence: 91%
“…Four patients had generalised pruritus with normal liver enzymes while repeat after one week, found to be elevated. Similar results were seen in two cases in the study done by Sharma N et al 10 Study conducted by Alakananda et al found serum bile acids and liver enzymes were raised in 100% cases. 13 It has been reported that itching may be presented either before or after abnormal liver function test and this may reflect the heterogeneous nature of this condition.…”
Section: Discussionsupporting
confidence: 86%
“…This study found that there was a significantly higher prevalence in South Asian, Indigenous Australian, and Asian ethnicity women amongst patients with ICP, with women from Indian and Pakistani ancestry representing 22.6% of our ICP population which is consistent with other published articles. [2][3][4] The results from this study indicated that the prevalence of ICP was significantly higher amongst those with a BMI greater than 35 kg/m 2 and significantly different when comparing overall group BMI (24.4 versus 25.5 kg/m 2 ). Gestational diabetes mellitus and pre-eclampsia are more common in women who are overweight or obese; 22 in our cohort, women with a BMI of greater than 35 kg/m 2 were more likely to have ICP.…”
Section: Main Findingsmentioning
confidence: 98%
“…The epidemiology of ICP is not well understood within Australia, although in English multi-ethnic pregnancies the incidence is believed to be 0.7%, 1 and 1.2-3.1% in patients of South Asian origin. [2][3][4] It appears the incidence is also influenced by genetics and environmental factors, with 2.4% of pregnancies in Chile affected, and a 5% prevalence in women of Araucanian-Indian origin. 5 Classically the condition presents with an unremitting pruritus, typically of the palms of the hands and soles of the feet and the diagnosis is confirmed biochemically with liver transaminase and/or bile acid elevation.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma N et al conducted an observational study in which diagnosed cases of IHCP were given medical and active management and observed lesser incidence of low (<7) APGAR score. 21…”
Section: Discussionmentioning
confidence: 99%